중소병원 야간교대근무 간호사의 수면의 질, 직무몰입, 웰니스의 관계 - 채여주; Yeojoo Chae; 고영심; Youngshim Go; 김지아; Jia Kim; 정채경; Chaecyeung Jeong; 이민희; Minhui Lee; 하영미; Yeongmi Ha (보건정보통계학회지, 2017)
Objectives: The purpose of this study was to identify the relationship between quality of sleep, job commitment, wellness, and identify contributing factors affecting on the wellness of night shift nurses in medium and small-sized hospitals. Methods: One hundred twenty four nurses who had working experiences with night shifts for 6 months or more completed a pack of questionnaires. Collected data were analyzed using t-test, ANOVA with Scheffe test, and stepwise multiple regression. Results: Factors including quality of sleep, job commitment, and wellness were identified. The quality of sleep score of the subject was 7.55(0-21), the job commitment was 20.17(7-35), and the wellness was 2.93(1-5). There was no significant in wellness according to general characteristics of subjects. The subjects' wellness had a significant negative correlation with quality of sleep(r=-0.31, p<0.001), and a significant positive correlation with job commitment(r=0.45, p<0.001). Regression analysis to identify factors affecting the wellness of night shift nurses showed that job commitment was the most significant factor (p<0.001), followed by quality of sleep(p=0.049). In the regression analysis, quality of sleep and job commitment were significant predictors and explained 21.9%(p<0.001) of wellness. Conclusions: Results of this study have suggested that job commitment and quality of sleep were significantly related to nurses' wellness in medium and small-sized hospitals. Therefore, there is a needed to develop a program with an enhancement of job commitment and a strategy of improving quality of sleep.